1917 Wis. Sess. Laws 1243-44, ch. 668, § 3, pt. 29.57 (4). - (:unkn) unknown (My University, 1917)
No owner of lands embraced within any such wild life refuge, and no other person whatever, shall hunt or trap within the boundaries of any wild life refuge, state park, or state fish hatchery lands; nor have in his possession or under his control therein any gun or rifle, unless the same is unloaded and knocked down or enclosed within its carrying case; but nothing herein shall prohibit, prevent, or interfere with the state conservation commission or its deputies agents or employees in the destruction of injurious animals.
Keywords: HUNTING REGULATION